Experimental investigation on integrated liquid desiccant – Indirect evaporative air cooling system utilizing the Maisotesenko – Cycle. (5th September 2015) - Gao, W.Z.; Cheng, Y.P.; Jiang, A.G.; Liu, T.; Anderson, Keith
Abstract: Liquid desiccant indirect evaporative cooling is an ideal alternative system for conventional vapor compression systems to meet new economic, environmental, and regulatory challenges. This alternative system consists of two air-handling processes: moisture removal in the dehumidifier and sensible heat removal in the M-cycle indirect evaporative cooler. The performance of the first stage influences the cooling capacity of the second stage. SHR (sensible load divided by total load), dew point effectiveness, moisture reduction, and temperature reduction were adopted as indices to describe the heat and mass transfer performance of the integrated liquid desiccant and the M-cycle indirect evaporative cooler. The effects of air and desiccant inlet parameters, as well as the working air ratio, on the performance of the hybrid were experimentally investigated. The results showed that the variation of dehumidification capacity in the first stage directly affected the cooling capacity in the second stage when increasing the inlet parameters of the air or desiccant. The energy balance in both the dehumidifier and the M-cycle indirect evaporative cooler were in the range of ±20% for all the experiment runs. To achieve performance in the second stage, the supplied water flow rate to the wick surface had to be approximately five times that of the evaporative water.